The Influence of Work Shift System, Work Pressure and Work Environment on Employee Performance Central Surgical Organization of Bhayangkara Hospital Kediri - Gian Alfreda Wirawan; Acep Samsudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine how the influence of the work shift system (X1), work pressure (X2), and work environment (X1) on employee performance (Y) Central Surgical Installation Bhayangkara Kediri Hospital. This type of research uses descriptive research using a quantitative approach. The population in this study was employees of the Central Surgical Installation of Bhayangkara Kediri Hospital, while the number of samples used was 40 respondents using saturated samples. Data analysis tools used in this study are validity test, classical assumption test, multiple linear regression analysis. The results of this study indicate that based on partial tests (1) Work Shift has no effect but has a significant value on employee performance (2) Work pressure has a positive effect on employee performance, (3) Work Environment has a significant positive effect on employee performance Central Surgical Installation Bhayangkara Kediri Hospital. (4) Work Shift, Work Pressure, and Work Environment simultaneously affect the performance of employees of the Central Surgical Installation of Bhayangkara Kediri Hospital.